Metafisika Filsafat dan Metafisika Menurut Ibn Arabi - Farhan, Baiq Dhiya’ul Husna (LP2M Universitas Islam Ahmad Dahlan, 2025)
Metaphysics, as a branch of philosophy, discusses everything that is fundamental. This is because the manifestation or reality of something is determined by its level of universality. Ibn Arabi, who received the title al-Syekh al-Akbar, is one of the great thinkers in Islam. His controversial thoughts on wahdat al-wujud have a great influence on the world of Islamic mysticism. This article is written based on library research to collect data from various literature sources. After the data was collected, the author applied a descriptive-analytical method to obtain the right conclusion. In the concept of metaphysics (Ma Ba'da al-Thabi'ah) according to Ibn Arabi, Allah is the main source of the four ma'lim, without anything behind it. It is called al-Wujud al-Muthlaq. The second ma'lum is the universal essence found in God and the universe, namely something that appears after creation, namely everything other than Allah Ta'ala. The third ma'lum covers the universe, including everything in the heavens and the earth, except humans. While the fourth ma'lum is humans as Allah's vicegerents on earth, which is also called the small world (microcosm). Meanwhile, the previous three ma'alim are known as the large world (macrocosm).